LEARNING METHOD TRAINING PROJECT BASED LEARNING (PBL) FOR STUDENTS STIT NAHDHATUL ULAMA AL FARABI PANGANDARAN - Suharyat, Yayat; Haryono, Pauzan; ., Baharuddin; Muthi, Ibn; Misbahul Alam, Dede Rubai (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
The purpose of this service activity is to provide knowledge and skills to prospective teachers of Islamic Religious Education at STIT NU Al Faraby Pangandaran in applying the Project Based Learning (PBL) learning method. The implementation of this service uses training and simulation methods including the provision of material, demonstrations, exercises, and simulations. Evaluation is carried out to determine the understanding and skills of trainees by comparing the results of the pre-test and post-test then analyzed quantitatively with the calculation of N-Gain. The results of this service show that prospective teachers who are students of the PIAUD STIT NU Al Faraby Study Program can apply the Project Based Learning (PBL) learning method with all learning steps well. With this activity, it is hoped that in the future prospective PIAUD teacher students can apply the PBL method directly in teaching practice (Teaching Internship Activities) besides that it can also directly increase confidence in carrying out their teaching duties after graduating at their respective workplaces.